Penguatan Daya Saing Kampung Gerabah Desa Pagelaran Melalui Analisis SWOT Dan 4P - Sindy Dinasti Bahrul Eltasari; Sifti Himmatus Suroiyah; Mohamad Bastomi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to determine an effective marketing strategy for pottery crafts in Pagelaran Village, Malang Regency. The approach used is a qualitative research approach. Data was collected through observation, interviews and documentation with sources. The inductive analysis method is used to conduct analysis on marketing strategies for pottery crafts. This interactive analysis model uses the SWOT method with the IFE and EFE matrices to determine business weaknesses and threats. Apart from analyzing using the SWOT method, namely the 4P strategy which has a big influence on pottery sales. The research results showed that the marketing strategy for pottery crafts in Pagelaran Village is currently still lacking. SWOT analysis shows that the strengths score is 2.12, weaknesses are 0.76, opportunities are 1.54, and threats are 0.87. The SWOT diagram shows the total score of the IFE matrix (2.88) and the EFE matrix (2.41) occupying quadrant 1 which supports the Aggressive Strategy. Aggressive strategies can support pottery craft businesses to take advantage of business opportunities and strengths. The 4P strategy elements identify the strengths of products produced in various shapes and prices according to the sizes ordered by consumers.